Parasitism disruption by ants of Anagyrus lopezi (Hymenoptera: Encyrtidae), parasitoid of cassava mealybug (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fanani MZ, Rauf A, Maryana N, Nurmansyah A, Hindayana D. 2020. Parasitism disruption by ants of Anagyrus lopezi (Hymenoptera: Encyrtidae), parasitoid of cassava mealybug. Biodiversitas 21: 2337-2343. Parasitoid, Anagyrus lopezi (De Santis) (Hymenoptera: Encyrtidae) was introduced into Indonesia in 2014 to control the invasive cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae). Among ants associated with honeydew-producing hemipterans, there are three common species in Indonesia i.e., Anoplolepis gracilipes (Smith), Dolichoderus thoracicus (Smith), and Oecophylla smaragdina (Fabricius) (Hymenoptera: Formicidae). The objective of this research was to investigate the relative influence of the three ant species on the parasitism of A. lopezi under laboratory conditions. Experiments were carried out by allowing a number of ants and parasitoids to forage on mealybugs-infested waterleaf (Talinum triangulare (Jaqc.) Willd.). The average time spent by individual parasitoid foraging was significantly longer (27.39 minutes) on ant-excluded plants compared to ant-attended plants (2.47- 4.68 minutes). Accordingly, parasitoid spent less time in finding hosts on ant-excluded plants, while spent a longer time in handling hosts. More oviposition activities by parasitoids on mealybug were occurred on ant-excluded plants compared to those on ant-attended plants. As a result, the percentage of parasitism and the number of wasps that emerged from the hosts on ant-excluded plants were almost 2 - 3 folds higher than those on ant-attended plants.
Keywords: Ants, biological control, biotic interference, cassava mealybug, parasitoid